A spatio‐temporal cluster analysis of technical efficiency in the production of outpatient maternal health services and its structural correlates in México. (12th June 2019) - Serván‐Mori, Edson; Mendoza, Miguel Ángel; Chivardi, Carlos; Pineda‐Antúnez, Carlos; Rodríguez‐Franco, Roxana; Nigenda, Gustavo
Summary: Objective: To analyze the formation of spatial clusters of technical efficiency (TE) in the production of outpatient maternal health services in México for the period 2008 to 2015. Methods: We performed a longitudinal analysis of administrative and structural data related to the 243 Mexican health jurisdictions. We use window data envelopment analysis and spatial and econometric techniques. Structural correlates of each TE cluster obtained were identified estimating a pooled multinomial logit model. Results: We observed an increase in the overall TE, accompanied by a reduction in its standard deviation. Furthermore, we identified positive TE spatial dependence both globally and locally. Multiple regression analysis showed that the maximum‐performance TE cluster was composed of health jurisdictions located in the North of México and characterized by social marginalization, a reduced indigenous population, and a low demand for maternal health services. Conclusions: The identification of TE clusters can provide elements to induce decision makers to innovative in ways of allocating resources and manage their utilization. In México as other low‐ and middle‐income countries, it is key to develop targeting strategies to implement specific health services innovations putting to the population to be served at the front of the strategy. This implies testing new modalities to strengthen primary health services, the empowerment of community participation, the training and allocation of health personnel that could respond adequately to population's demand, and the active involvement of competent state and local authorities in the assessment of the results of these innovations.